Preparation method of crosslinked shielding material for direct current cable

CN122917433APending Publication Date: 2026-10-16JIANGSU DONGFANG CABLE MATERIAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611407885.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,由于EBA分子链中丙烯酸丁酯结构单元的酯基烷基链较长,其与碳系导电填料表面的界面相互作用较弱,填料在基体中的分散均匀性和界面结合强度有待提高,进而影响导电网络的均匀性和长期稳定性

Benefits of technology

[0021] The present invention has at least one of the following technical effects: 1. The present invention forms a conductive bridging layer by in-situ gas-phase polymerization of poly(3,4-ethylenedioxythiophene) on the surface of carbon-based fillers, combined with the one-dimensional synergistic bridging effect of carboxylated multi-walled carbon nanotubes and the interfacial compatibilization effect of maleic anhydride-grafted ethylene-butyl acrylate copolymer, thereby significantly reducing the volume resistivity of cross-linked shielding material with a relatively large total filler content, while effectively improving the stability of resistivity at high temperature and significantly enhancing the resistance to thermal aging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917433A_ABST
    Figure CN122917433A_ABST
Patent Text Reader

Abstract

The application relates to the field of power cable material preparation, in particular to a preparation method of a crosslinked shielding material for a direct current cable. After the conductive carbon black and carboxylated multi-walled carbon nanotubes are dispersed, spray drying is carried out to form porous particles, the porous particles are sprayed into an iron p-toluenesulfonate solution twice, vacuum drying is carried out, 3,4-ethylenedioxythiophene vapor is introduced for gas phase polymerization, and a PEDOT bridging type carbon conductive filler is obtained; the filler is mixed with ethylene-butyl acrylate copolymer and maleic anhydride grafted ethylene-butyl acrylate copolymer at <= 110 DEG C to obtain a conductive master batch; the conductive master batch is mixed with the remaining ethylene-butyl acrylate copolymer, an antioxidant and a lubricant, a peroxide crosslinking agent and a crosslinking sensitizer are added after cooling, and mixing, granulation and the like are carried out to obtain the crosslinked shielding material. The application reduces the volume resistivity, effectively inhibits the PTC effect, improves the thermal stability and anti-aging performance of the conductive connection structure, and is suitable for a high-voltage direct current cable shielding layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of power cable material preparation technology, specifically a method for preparing cross-linked shielding material for DC cables. Background Technology

[0002] High-voltage direct current (HVDC) cables are key equipment for large-scale renewable energy grid connection and inter-regional power transmission. In the structure of a DC cable, a semi-conductive shielding layer is located between the conductor and the insulation layer, and on the outside of the insulation layer. Its core function is to eliminate electric field concentration caused by burrs on the conductor surface, ensure a uniform electric field distribution at the insulation layer interface, and suppress partial discharge and insulation breakdown. Semi-conductive shielding materials are typically composed of a matrix resin, conductive filler, crosslinking agent, and processing aids. The stability and uniformity of the shielding layer's volume resistivity are crucial indicators determining the cable's operational reliability and service life.

[0003] Currently, traditional shielding materials use conductive carbon black as the main conductive filler, typically requiring 20–40 parts by weight to form an effective conductive network. High filler content often leads to deterioration in material processing performance and a decrease in mechanical properties. To further reduce the percolation threshold and improve the stability of the conductive network, existing technologies attempt to introduce carbon nanotubes as auxiliary fillers, utilizing their one-dimensional high aspect ratio structure to bridge carbon black aggregates and construct composite conductive pathways. However, the interaction between carbon nanotubes and carbon black is only physical, with weak interfacial bonding. Under the thermal-shear stress of long-term thermal aging and cross-linking reactions, the conductive network is prone to reconstruction or even local fracture, resulting in a significant positive temperature coefficient (PTC) effect in volume resistivity and a substantial increase in resistivity after aging. This severely affects the electric field homogenization effect under high-temperature conditions and the long-term operational reliability of cables.

[0004] Regarding the matrix resin, early shielding materials mostly used ethylene-vinyl acetate copolymer (EVA), but its thermal decomposition temperature is only about 240℃, and its performance deteriorates rapidly after long-term thermal aging. Ethylene-butyl acrylate copolymer (EBA), with a thermal decomposition temperature as high as 330℃, has excellent thermal stability and is an ideal matrix resin for high-voltage / ultra-high-voltage shielding materials. However, due to the long alkyl chain of the butyl acrylate structural unit in the EBA molecular chain, its interfacial interaction with the surface of the carbon-based conductive filler is weak. The uniformity of filler dispersion and interfacial bonding strength in the matrix need to be improved, which in turn affects the uniformity and long-term stability of the conductive network. At the same time, the conductive filler-matrix interface in existing shielding materials relies only on physical entanglement and weak van der Waals forces, lacking functional interface layer design. Under the shear and thermal stress conditions of crosslinking reactions, the filler network is prone to irreversible reconstruction, leading to a decrease in conductivity stability.

[0005] Therefore, the present invention provides a method for preparing cross-linked shielding material for DC cables to improve the interfacial bonding strength and thermal stability of the conductive network, suppress the PTC effect, and improve the dispersion uniformity of the filler in the EBA matrix, thereby meeting the requirements of high voltage / ultra-high voltage DC cables for the comprehensive performance of the shielding material. Summary of the Invention

[0006] To address the aforementioned problems, this invention provides a method for preparing cross-linked shielding material for DC cables, comprising the following steps: S1. By weight, 20-35 parts of conductive carbon black and 1-4 parts of carboxylated multi-walled carbon nanotubes are sheared and dispersed in 400-750 parts of an ethanol / water mixed solution. After spray drying, the mixture is lightly granulated using a roller press. The rolling pressure is 2-8 MPa, the roller gap is 0.5-1.5 mm, the roller speed is 5-15 rpm, and the rolling is repeated 1-3 times to obtain porous particles. The wettable pore volume per unit mass is determined by mercury intrusion porosimetry. 6-10 wt% of an organic sulfonate iron salt is weighed according to the total mass of the conductive carbon black and carboxylated multi-walled carbon nanotubes. 30%-40% of the total organic sulfonate iron salt is prepared into an organic sulfonate iron salt solution with a mass concentration of 10%-15%. The total wettable pore volume of the porous particles (total wettable pore volume = wettable pore volume per unit mass) is then used to determine the wettable pore volume. 20%–30% of the volume of the carbon-based filler (by mass) is sprayed into the particles, agitated, and then dried under reduced pressure. The remaining 60%–70% of the organic sulfonate iron salt is then prepared into an organic sulfonate iron salt solution with a mass concentration of 25%–35%, and sprayed into the particles at a volume of 20%–30% of the total wettable pore volume of the porous particles. After agitation and reduced pressure drying, composite particles are obtained. 3,4-ethylenedioxythiophene (EDOT) vapor is introduced at 4–20 kPa and 40–80 °C, and reacted with the composite particles for 60–180 min. The mass ratio of the total 3,4-ethylenedioxythiophene feed to the total amount of organic sulfonate iron salt is (0.36–0.72):1. After impregnation with the oxidant, 3,4-ethylenedioxythiophene undergoes in-situ vapor-phase polymerization on the surface and contact interface of the carbon-based filler to form a PEDOT bridging layer. After washing and drying, a PEDOT-bridged carbon-based conductive filler is obtained.

[0007] The porous particles have an average pore size of 50–500 nm. The porous particles prepared by spray drying have an interconnected pore structure inside, with carbon fillers in contact with each other inside the particles. This pore structure is beneficial for the penetration of the oxidant solution and the diffusion and mass transfer of 3,4-ethylenedioxythiophene vapor. The wettable pore volume per unit mass is an operational parameter determined by the following mercury intrusion porosimetry method: the sample is weighed after vacuum drying at 80 °C for 2 h, placed in a dilatometer, and mercury is introduced in stages at low pressure (0.5–30 psi) and high pressure (30–60000 psi). The contact angle of the mercury intrusion porosimeter is set to 130°, and the surface tension of mercury is taken as 485 mN / m. The pressure-mercury intrusion curve is recorded, and the cumulative mercury intrusion volume with a pore size greater than 10 nm is divided by the sample mass to obtain the wettable pore volume per unit mass, expressed in mL / g. This value is only used as a reference amount to determine the amount of oxidant solution sprayed in this application.

[0008] By controlling the volume of each spray to 20%–30% of the total wettable pore volume, and the total volume of two sprays to 40%–60% of the total wettable pore volume, the oxidant can form a certain degree of decreasing content distribution from the surface to the inside of the particle, avoiding filling all the pores at once. This allows the 3,4-ethylenedioxythiophene vapor to gradually penetrate to different depths inside the particle during subsequent gas-phase polymerization, preventing the vapor mass transfer from being hindered by the pores being completely occupied by the solution.

[0009] The reduced pressure conditions (4-20 kPa) are set to lower the evaporation temperature of 3,4-ethylenedioxythiophene (the boiling point of 3,4-ethylenedioxythiophene at normal pressure is about 200°C), so as to avoid thermal disturbance to the distribution of the oxidant already loaded inside the carbon filler due to high temperature. At the same time, the reduced pressure environment is conducive to the rapid penetration of 3,4-ethylenedioxythiophene vapor into the internal pores of the porous particles.

[0010] S2. The total amount of ethylene-butyl acrylate copolymer is 80-90 parts. Take 25-40 parts of the ethylene-butyl acrylate copolymer and mix it with the PEDOT bridging carbon conductive filler. Add maleic anhydride-grafted ethylene-butyl acrylate copolymer as a compatibilizer to prepare conductive masterbatch. The amount of maleic anhydride-grafted ethylene-butyl acrylate copolymer is 5-15% of the total mass of ethylene-butyl acrylate copolymer.

[0011] S3. The conductive masterbatch is mixed with the remaining ethylene-butyl acrylate copolymer, and antioxidants, lubricants, peroxide crosslinking agents and crosslinking sensitizers are added. After mixing, the mixture is discharged and granulated to obtain crosslinked shielding material.

[0012] Preferably, in S1, the mass ratio of ethanol to water in the ethanol / water mixed solution is (5-9):1; the inlet air temperature of the spray drying is 120-180℃, and the outlet air temperature is 60-90℃; after each spraying, the mixture is turned over for 5-10 minutes and pre-dried under reduced pressure at 40-50℃ for 15-30 minutes.

[0013] Preferably, in S1, the conductive carbon black has a particle size of 30-50 nm; the carboxylated multi-walled carbon nanotubes have a carboxyl content of 0.5-5 wt%, an outer diameter of 8-15 nm, and a length of 5-15 μm.

[0014] Preferably, in S1, the organic ferric sulfonate is ferric p-toluenesulfonate (calculated as anhydrous); the solvent of the organic ferric sulfonate solution is n-butanol or a n-butanol / ethanol mixed solvent, wherein the volume ratio of n-butanol to ethanol in the n-butanol / ethanol mixed solvent is (0.8~1.2):1.

[0015] Preferably, in S1, the 3,4-ethylenedioxythiophene vapor is generated by heating the 3,4-ethylenedioxythiophene monomer to 80-120°C through an independent heating chamber, and an inert gas is introduced as the carrier gas; after the contact is completed, the temperature is raised to 80-100°C at a rate of 1-5°C / min for post-treatment for 10-30min; the pressure under the depressurization condition is 4-20kPa.

[0016] Preferably, in S1, the washing involves washing with anhydrous ethanol 2 to 4 times and deionized water 3 to 5 times in sequence to remove residual iron salts and byproducts, until the pH of the final washing solution is 6.5 to 7.5.

[0017] Preferably, the butyl acrylate content in the ethylene-butyl acrylate copolymer is 15-22 wt%, and the grafting rate of the maleic anhydride-grafted ethylene-butyl acrylate copolymer is 0.8-1.5%.

[0018] Preferably, the antioxidant is a compound of hindered phenolic antioxidants and phosphite antioxidants; the lubricant is a polyol fatty acid ester; the peroxide crosslinking agent is a dialkyl peroxide; and the crosslinking sensitizer is an allyl compound.

[0019] Preferably, the hindered phenolic antioxidant is antioxidant 1010, the phosphite antioxidant is antioxidant 168, and the mass ratio of the two is (0.8-1.2):1, with a total antioxidant dosage of 0.25-0.45 parts; the polyol fatty acid ester is pentaerythritol stearate, with a dosage of 0.25-0.9 parts; the dialkyl peroxide is 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, with a dosage of 1-2 parts; and the allyl compound is triallyl isocyanurate, with a dosage of 0.3-0.8 parts.

[0020] Preferably, in step S2, after the ethylene-butyl acrylate copolymer and maleic anhydride-grafted ethylene-butyl acrylate copolymer are preplasticized, the PEDOT bridging carbon-based conductive filler is added and the mixture is kneaded at a temperature not exceeding 110°C; in step S3, the peroxide crosslinking agent and crosslinking sensitizer are added after the kneading temperature drops below 110°C.

[0021] The present invention has at least one of the following technical effects: 1. The present invention forms a conductive bridging layer by in-situ gas-phase polymerization of poly(3,4-ethylenedioxythiophene) on the surface of carbon-based fillers, combined with the one-dimensional synergistic bridging effect of carboxylated multi-walled carbon nanotubes and the interfacial compatibilization effect of maleic anhydride-grafted ethylene-butyl acrylate copolymer, thereby significantly reducing the volume resistivity of cross-linked shielding material with a relatively large total filler content, while effectively improving the stability of resistivity at high temperature and significantly enhancing the resistance to thermal aging.

[0022] 2. This invention, through process control of low-temperature mixing and the addition of crosslinking agents after cooling, combined with the homogenization and promotion of the crosslinking reaction by poly(3,4-ethylenedioxythiophene) bridging carbon filler, enables the crosslinked shielding material to achieve high crosslinking degree within a wide formulation window, while also exhibiting good thermal elongation properties and mechanical strength.

[0023] 3. This invention significantly improves the dispersion uniformity of conductive fillers in the ethylene-butyl acrylate copolymer matrix through the synergistic effect of poly(3,4-ethylenedioxythiophene)-bridged carbon filler and maleic anhydride-grafted ethylene-butyl acrylate copolymer compatibilizer, effectively inhibiting filler agglomeration, thereby obtaining a smooth molding surface and maintaining good processing performance. Attached Figure Description

[0024] Figure 1 These are the TEM morphology and EDS elemental distribution diagrams of the PEDOT bridging carbon-based conductive filler prepared in Example 1 of this invention. Figure 2 This is a SEM image of the cross-section of the conductive masterbatch prepared in Example 1 of this invention; Figure 3 This is a graph showing the change in volume resistivity of the crosslinked shielding layer prepared in Examples 1, 10, 4 and 1 of the present invention as a function of temperature. Detailed Implementation

[0025] The present invention will now be described in detail through specific embodiments. However, these illustrative embodiments are for purposes and uses only to illustrate the invention and do not constitute any limitation on the actual scope of protection of the invention, nor are they intended to limit the scope of protection of the invention to these embodiments. All equivalent transformations or simple substitutions made based on the substantive content of this application should fall within the scope of protection of this application. For parameter ranges not mentioned, intermediate values ​​are selected. Furthermore, for mass percentages or weight percentages not explicitly stated or mentioned, they generally refer to the final concentration after addition.

[0026] The singular forms “for,” “or,” “a,” “any,” and “the” used in this application are intended to include the plural forms unless the context clearly indicates otherwise.

[0027] The combination of two spraying processes and reduced-pressure drying creates a non-uniform distribution of ferric p-toluenesulfonate within the porous particles, from the surface inwards. This helps provide catalytically active sites at different depths within the particles, facilitating uniform subsequent gas-phase polymerization. 3,4-Ethylenedioxythiophene vapor penetrates deep into the pores of the particles, where, under the oxidation of ferric p-toluenesulfonate, it polymerizes in situ on the surface of the carbon-based filler to form a poly-3,4-ethylenedioxythiophene bonding layer. For example... Figure 1 Transmission electron microscopy (TEM) and EDS elemental analysis showed that poly(3,4-ethylenedioxythiophene) (PEDOT) formed continuously distributed conductive regions on the surfaces of carbon black particles and carboxylated multi-walled carbon nanotubes (MWCNTs), and constructed a bridging structure at the carbon black-carbon nanotube interface. This facilitates the connection of carbon-based fillers into a more stable conductive connection structure, reduces the contact resistance between fillers, and decreases the probability of interruption of the conductive pathway under thermal stress. The carboxyl functional groups on the surface of carboxylated MWCNTs improved their stability in the dispersion system. It is speculated that the presence of carboxyl groups may be beneficial to the uniform polymerization of 3,4-ethylenedioxythiophene, enabling PEDOT to form a connecting layer on the surface of the carbon nanotubes and at the contact interface.

[0028] The main chain of the maleic anhydride-grafted ethylene-butyl acrylate copolymer is ethylene-butyl acrylate structure, which has excellent compatibility with the ethylene-butyl acrylate copolymer matrix resin and can be uniformly dispersed in the matrix. As a polar reactive functional group, the anhydride group may enhance the filler-matrix interface bonding through the following multiple mechanisms: (1) the anhydride group forms an ion-dipole interaction with the sulfonate groups doped in the PEDOT bridging layer; (2) the anhydride group forms hydrogen bonds with the carboxyl groups on the surface of carboxylated multi-walled carbon nanotubes; (3) the anhydride group may interact with the oxygen-containing functional groups on the surface of PEDOT segments or carbon nanotubes during the mixing process; (4) the chain entanglement between the maleic anhydride-grafted ethylene-butyl acrylate copolymer molecular chain and the matrix ethylene-butyl acrylate copolymer molecular chain. By controlling the mixing temperature below 110℃ and adding the crosslinking agent after cooling, the premature thermal decomposition of the peroxide crosslinking agent and the early crosslinking caused by it are avoided, ensuring that the activity of the crosslinking agent is fully utilized in the molding stage and obtaining a uniform and sufficient crosslinked structure.

[0029] In summary, this invention, through the structural design of the PEDOT-bridged carbon-based conductive filler and the interfacial compatibilization effect of maleic anhydride-grafted ethylene-butyl acrylate copolymer, facilitates the construction of a stable conductive connection network and improves filler dispersion, enabling the crosslinked shielding material to achieve low volume resistivity, high crosslinking degree, and good processing performance.

[0030] In the embodiments of this application, the anhydrous ferric p-toluenesulfonate (molecular formula: (CH3C6H4SO3)3Fe, molecular weight: 569.4, purity ≥98%) weighed refers to the actual amount weighed on an anhydrous basis, which is the total amount of anhydrous ferric p-toluenesulfonate used to prepare the two sprayed stock solutions, calculated as 6-10 wt% of the total mass of the carbon-based packing. When the ferric p-toluenesulfonate solution is sprayed in a "partial spraying" operation (i.e., the sprayed volume is less than the total volume of the prepared solution), the actual mass of ferric p-toluenesulfonate sprayed onto the porous particles can be calculated by multiplying the weighed amount by the ratio of the sprayed volume to the total prepared volume.

[0031] Example Example 1 S1. By weight, 28g of conductive carbon black (particle size 40nm) and 2.5g of carboxylated multi-walled carbon nanotubes (outer diameter 12nm, length 10μm) were sheared and dispersed in 575g of an ethanol / water mixed solution (503g ethanol, 72g water). After spray drying at an inlet air temperature of 150℃ and an outlet air temperature of 75℃, the particles were lightly granulated by roller pressing at 5MPa with a roller gap of 1mm and a roller speed of 10rpm. The resulting porous particles weighed 25.3g. 2g of porous particles were subjected to a mercury porosimeter to determine the wettable pore volume per unit mass (the cumulative mercury ingress volume of particles with a pore size greater than 10nm was divided by the sample mass). The result was 0.75mL / g. Therefore, the total wettable pore volume was 25.32×0.75=18.99mL. Anhydrous ferric p-toluenesulfonate (calculated as anhydrous, purity ≥98%) was weighed out as 8wt% of the total mass of the conductive carbon black and carboxylated multi-walled carbon nanotubes. That is, the total amount of ferric p-toluenesulfonate was 2.44g.

[0032] First spraying: Weigh 0.854g of anhydrous ferric p-toluenesulfonate (35% of the total anhydrous ferric p-toluenesulfonate), 2.52g of n-butanol, and 2.52g of ethanol to prepare a ferric p-toluenesulfonate solution. Take 4.75mL and spray it into the granules. After stirring for 7 minutes, pre-dry under reduced pressure at 45℃ for 22 minutes. Second spraying: Take the remaining 1.586g of anhydrous ferric p-toluenesulfonate, and prepare a ferric p-toluenesulfonate solution with 1.85g of n-butanol and 1.85g of ethanol. Take 5.7mL and spray it into the granules. After stirring for 7 minutes, pre-dry under reduced pressure at 45℃ for 22 minutes to obtain composite granules.

[0033] 1.31 g of 3,4-ethylenedioxythiophene vapor (generated in an independent heating chamber heated to 100°C with nitrogen as the carrier gas at a flow rate of 50 mL / min) was introduced at 12 kPa and 60°C and reacted with the composite particles for 120 min. The 1.31 g represents the actual mass of EDOT introduced, determined by the difference in weight before and after the reaction in the heating chamber (under these conditions, the EDOT evaporation and transport efficiency is ≥98%). After the contact, the temperature was increased to 90°C at a rate of 3°C / min and held for 20 min for post-treatment. After the reaction, the particles were washed three times with ethanol and four times with deionized water until the pH of the final washing solution was 7.0. After vacuum drying at 80°C, PEDOT-bridged carbon-based conductive filler was obtained.

[0034] S2. 33g of ethylene-butyl acrylate copolymer and 8.5g of maleic anhydride-grafted ethylene-butyl acrylate copolymer are pre-plasticized in a mixer at 100℃ for 2min. The above-mentioned PEDOT bridging carbon-based conductive filler is added, and the mixture is further mixed at 105℃ for 8min. The mixture is then discharged and granulated by a twin-screw extruder (barrel temperature in all zones ≤110℃) to obtain conductive masterbatch.

[0035] S3. The conductive masterbatch is mixed with 52g of ethylene-butyl acrylate copolymer, and 0.175g of antioxidant 1010, 0.175g of antioxidant 168 and 0.6g of pentaerythritol stearate are added. The mixture is mixed at 100℃ for 3 minutes, then cooled to 95℃, and 1.5g of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane and 0.55g of triallyl isocyanurate are added. The mixture is then mixed for another 4 minutes, with the total mixing temperature not exceeding 105℃ throughout the process. The material is discharged and extruded into granules (barrel temperature settings: feeding zone 90℃, compression section 100℃, metering section 105℃, die head 105℃) to obtain the crosslinked shielding material.

[0036] Example 2 The difference from Example 1 is as follows: In S1, the amount of conductive carbon black used is 20g, the total wettable pore volume is 13.84mL, the total amount of anhydrous ferric p-toluenesulfonate is 1.8g, the first spraying solution is prepared by weighing 35% of the total amount of anhydrous ferric p-toluenesulfonate, i.e., 0.63g, and mixing it with 1.94g of n-butanol and 1.93g of ethanol, and spraying 3.46mL of the solution into the container; the second spraying solution is prepared by mixing the remaining 1.17g of anhydrous ferric p-toluenesulfonate with 1.51g of n-butanol and 1.5g of ethanol, and spraying 4.15mL of the solution into the container; the amount of 3,4-ethylenedioxythiophene used is 0.97g, and the rest of the preparation method is the same as in Example 1.

[0037] Example 3 The difference from Example 1 is as follows: In S1, the amount of conductive carbon black used is 35g, the total wettable pore volume is 23.63mL, the total amount of anhydrous ferric p-toluenesulfonate is 3g, the first spraying solution: 35% of the total amount of anhydrous ferric p-toluenesulfonate, i.e., 1.05g, is weighed and mixed evenly with 2.98g of n-butanol and 2.97g of ethanol to prepare a ferric p-toluenesulfonate solution, and 7.09mL is sprayed in; the second spraying solution: the remaining 1.95g of anhydrous ferric p-toluenesulfonate is mixed evenly with 2.39g of n-butanol and 2.38g of ethanol to prepare a ferric p-toluenesulfonate solution, and 7.09mL is sprayed in; the amount of 3,4-ethylenedioxythiophene used is 1.62g, and the rest of the preparation method is the same as in Example 1.

[0038] Example 4 The difference from Example 1 is as follows: In S1, the amount of carboxylated multi-walled carbon nanotubes used is 1g, the total wettable pore volume is 18.49mL, the total amount of anhydrous ferric p-toluenesulfonate is 2.32g, the first spraying solution is prepared by weighing 35% of the total amount of anhydrous ferric p-toluenesulfonate, i.e., 0.812g, and mixing it with 2.5g of n-butanol and 2.49g of ethanol, and taking 5.18mL of the solution for spraying; the second spraying solution is prepared by mixing the remaining 1.508g of anhydrous ferric p-toluenesulfonate with 1.94g of n-butanol and 1.94g of ethanol, and taking 5.55mL of the solution for spraying; the amount of 3,4-ethylenedioxythiophene used is 1.25g, and the rest of the preparation method is the same as in Example 1.

[0039] Example 5 The difference from Example 1 is as follows: In S1, the amount of carboxylated multi-walled carbon nanotubes used is 4g, the total wettable pore volume is 19.44mL, the total amount of anhydrous ferric p-toluenesulfonate is 2.56g, the first spraying solution is prepared by weighing 35% of the total amount of anhydrous ferric p-toluenesulfonate, i.e., 0.896g, and mixing it with 2.54g of n-butanol and 2.54g of ethanol, and spraying 5.44mL of the solution; the second spraying solution is prepared by mixing the remaining 1.664g of anhydrous ferric p-toluenesulfonate with 1.94g of n-butanol and 1.94g of ethanol, and spraying 5.83mL of the solution; the amount of 3,4-ethylenedioxythiophene used is 1.38g, and the rest of the preparation method is the same as in Example 1.

[0040] Example 6 The difference from Example 1 is that the total amount of 3,4-ethylenedioxythiophene supplied in S1 and the total amount of anhydrous ferric p-toluenesulfonate are weighed in a mass ratio of 0.36:1, that is, the amount of 3,4-ethylenedioxythiophene used is 0.88g, and the rest of the preparation method is the same as in Example 1.

[0041] Example 7 The difference from Example 1 is that the mass ratio of the total amount of 3,4-ethylenedioxythiophene supplied in S1 to the total amount of anhydrous ferric p-toluenesulfonate is 0.72:1, that is, the amount of 3,4-ethylenedioxythiophene used is 1.76g, and the rest of the preparation method is the same as in Example 1.

[0042] Example 8 The difference from Example 1 is as follows: In S1, the total amount of anhydrous ferric p-toluenesulfonate is 6 wt%, or 1.83 g, of the total mass of the carbon-based filler. For the first spraying: 35% of the total amount of anhydrous ferric p-toluenesulfonate, or 0.641 g, is weighed and mixed with 2.35 g of n-butanol and 2.35 g of ethanol to prepare a ferric p-toluenesulfonate solution, and 4.75 mL is sprayed in. For the second spraying: the remaining 1.189 g of anhydrous ferric p-toluenesulfonate is mixed with 1.79 g of n-butanol and 1.78 g of ethanol to prepare a ferric p-toluenesulfonate solution, and 4.75 mL is sprayed in. The amount of 3,4-ethylenedioxythiophene used is 0.988 g, and the rest of the preparation method is the same as in Example 1.

[0043] Example 9 The difference from Example 1 is as follows: In S1, the total amount of anhydrous ferric p-toluenesulfonate is 10wt% of the total mass of the carbon-based filler, i.e., 3.05g. For the first spraying: 35% of the total amount of anhydrous ferric p-toluenesulfonate, i.e., 1.068g, is weighed and mixed evenly with 3.03g of n-butanol and 3.02g of ethanol to prepare a ferric p-toluenesulfonate solution, and 4.75mL is sprayed in. For the second spraying: the remaining 1.982g of anhydrous ferric p-toluenesulfonate is mixed evenly with 2.11g of n-butanol and 2.1g of ethanol to prepare a ferric p-toluenesulfonate solution, and 5.70mL is sprayed in. The amount of 3,4-ethylenedioxythiophene used is 1.647g, and the rest of the preparation method is the same as in Example 1.

[0044] Example 10 The difference from Example 1 is that in S1, the inlet air temperature of the spray drying is set to 130℃, the outlet air temperature is set to 65℃, the weight of the obtained porous particles is 25.01g, and the wettable pore volume per unit mass determined by mercury porosimetry is 0.48mL / g, so the total wettable pore volume = 25.01 × 0.48 = 12.00mL. For the first spray, 3.00mL of ferric p-toluenesulfonate solution is sprayed in, and for the second spray, 3.60mL of ferric p-toluenesulfonate solution is sprayed in. The remaining preparation methods are the same as in Example 1.

[0045] Example 11 The difference from Example 1 is as follows: In S1, the inlet air temperature of the spray drying is set to 180℃, the outlet air temperature is set to 90℃, the weight of the obtained porous particles is 25.62g, and the wettable pore volume per unit mass determined by mercury porosimetry is 1.15mL / g, the total wettable pore volume = 25.62 × 1.15 = 29.46mL. First spray solution: Weigh 0.854g of anhydrous ferric p-toluenesulfonate and mix it with 2.62g of n-butanol and 2.63g of ethanol to prepare a ferric p-toluenesulfonate solution, and spray 7.22mL into the solution; Second spray solution: Take the remaining 1.586g of anhydrous ferric p-toluenesulfonate and mix it with 2.09g of n-butanol and 2.04g of ethanol to prepare a ferric p-toluenesulfonate solution, and spray 6.38mL into the solution. The remaining preparation methods are the same as in Example 1.

[0046] Comparative Example Comparative Example 1 The difference from Example 1 is that the conductive carbon black and carboxylated multi-walled carbon nanotubes in S1 are not dispersed, spray-dried, rolled and granulated, impregnated with oxidant and gas-phase polymerized with 3,4-ethylenedioxythiophene, but are directly physically mixed and used as carbon-based conductive fillers in S2. The rest of the preparation methods are the same as in Example 1.

[0047] Comparative Example 2 The difference from Example 1 is that in S1, after conductive carbon black and carboxylated multi-walled carbon nanotubes are sheared, dispersed, spray-dried and lightly rolled to obtain porous particles, they are not subjected to anhydrous iron p-toluenesulfonate impregnation and 3,4-ethylenedioxythiophene gas-phase polymerization treatment. Instead, the obtained porous particles are directly used as carbon-based conductive fillers in S2. The rest of the preparation methods are the same as in Example 1.

[0048] Comparative Example 3 The difference from Example 1 is that in S1, the conductive carbon black and carboxylated multi-walled carbon nanotubes are not spray-dried and rolled into granules, but are directly mixed with the iron p-toluenesulfonate solution in their original powder state. All the anhydrous iron p-toluenesulfonate is prepared into an iron p-toluenesulfonate solution (2.44 g of anhydrous iron p-toluenesulfonate, 4.46 g of n-butanol, and 4.35 g of ethanol) and added at once (without two gradient sprayings). The rest of the preparation method is the same as in Example 1.

[0049] Comparative Example 4 The difference from Example 1 is that in S1, all anhydrous ferric p-toluenesulfonate was prepared into a ferric p-toluenesulfonate solution (2.44 g of anhydrous ferric p-toluenesulfonate, 4.46 g of n-butanol, and 4.35 g of ethanol) in one go, and sprayed into the porous particles in one go. After turning, it was pre-dried under reduced pressure at 45°C for 22 min, and no second spraying was performed; the rest of the preparation method is the same as in Example 1.

[0050] Comparative Example 5 The difference from Example 1 is that carboxylated multi-walled carbon nanotubes are not added in S1, but are replaced with an equal mass of conductive carbon black (keeping the total mass of carbon filler consistent with Example 1), and the rest of the preparation method is the same as in Example 1.

[0051] Comparative Example 6 The difference from Example 1 is that the multi-walled carbon nanotubes in S1 are unmodified original multi-walled carbon nanotubes, and the rest of the preparation methods are the same as in Example 1.

[0052] Comparative Example 7 The difference from Example 1 is that maleic anhydride-grafted ethylene-butyl acrylate copolymer is not added in S2, while the rest of the preparation method is the same as in Example 1.

[0053] Comparative Example 8 The difference from Example 1 is that the amount of 3,4-ethylenedioxythiophene used in S1 is 0.22g, that is, the mass ratio of 3,4-ethylenedioxythiophene / anhydrous p-toluenesulfonate ferric is about 0.09:1. The rest of the preparation method is exactly the same as in Example 1.

[0054] Comparative Example 9 The difference from Example 1 is that the amount of 3,4-ethylenedioxythiophene used in S1 is 2.44g, that is, the mass ratio of 3,4-ethylenedioxythiophene to anhydrous p-toluenesulfonate ferric is 1:1. The rest of the preparation method is exactly the same as in Example 1.

[0055] The morphology of the PEDOT-bridged carbon-based conductive filler prepared in step S1 of Example 1 was observed using transmission electron microscopy, and elemental surface scanning analysis was performed using energy-dispersive X-ray spectroscopy. The results are as follows: Figure 1 As shown.

[0056] The morphology of the cross-section of the conductive masterbatch prepared in step S2 of Example 1 was observed using a scanning electron microscope, and the results are as follows: Figure 2 As shown.

[0057] The crosslinked shielding materials prepared in Examples 1-11 and Comparative Examples 1-9 were hot-pressed and crosslinked at 180°C and 15MPa for 15 minutes on a flat vulcanizing machine to obtain a crosslinked shielding layer. The layer was then cooled to room temperature under pressure at 10MPa and cut into 1mm thick sheets and standard dumbbell-shaped samples. The above samples were subjected to the following tests, and the performance test results are shown in Table 1.

[0058] Thin films with a thickness of 1 mm prepared in Examples 1, 10, Comparative Example 4, and 1 were used, with three parallel samples in each group. Following the electrode arrangement specified in GB / T3048.3-2007, the samples were fixed in the high-temperature testing fixture of a semiconducting resistivity tester (DB-4, Shanghai Changbao Testing Instruments Co., Ltd.), and the actual temperature of the samples was monitored using a thermocouple-equipped temperature-controlled element of the same material. Tests were conducted at room temperature (23±2℃), 30℃, 40℃, 50℃, 60℃, 70℃, 80℃, and 90℃, with a temperature increase rate of 10℃ / min between adjacent temperature points. After the actual temperature reached the target temperature ±1℃, it was held at that temperature for 10 minutes. After the temperature and instrument readings stabilized, three consecutive measurements were taken, and the average value was recorded. A graph was plotted between the average volume resistivity of the three parallel samples and the actual temperature to obtain the... Figure 3 The volume resistivity-temperature curve shown is as follows. Figure 3 The curve in the figure represents the trend line connecting the average volume resistivity at each test temperature point.

[0059] Performance Test 1 Volume resistivity: Referring to GB / T3048.3-2007, the volume resistivity at room temperature (23±2℃) and 90℃ was tested using the four-probe method. Five test points were taken for each sample and the average value was calculated.

[0060] Performance Test 2 Gel content: According to GB / T18474-2001, the cross-linked sheet was cut into pieces, and about 0.5g of sample was accurately weighed. The sample was wrapped in a 200-mesh stainless steel mesh and extracted by reflux in xylene for 24h. After being taken out, it was dried in a vacuum oven to constant weight, and the gel content was calculated.

[0061] Performance Test 3 Tensile strength and elongation at break: In accordance with GB / T2951.11-2008 standard, the dumbbell-shaped specimen was subjected to tensile testing using a universal tensile testing machine at a tensile rate of 250 mm / min.

[0062] Performance Test 4 Thermal elongation test: According to GB / T2951.21-2008, a load of 0.2MPa was applied to the dumbbell-shaped specimen at 200℃ and held for 15min. The thermal elongation and permanent deformation rate after cooling were measured.

[0063] Performance Test 5 Volume resistivity thermal stability: Referring to GB / T2951.12-2008, the sample was aged in an oven at 120℃ for 240h, and the volume resistivity at room temperature was tested again. The change rate of volume resistivity after aging was calculated. Change rate of resistivity after aging = (volume resistivity at room temperature after aging - volume resistivity at room temperature before aging) / volume resistivity at room temperature before aging × 100%.

[0064] Performance Test 6 Surface roughness: Referring to GB / T14234-1993 and GB / T1031-2009, the surface roughness Ra value of the cross-linked sheet was measured using a stylus profilometer. The average value was taken at three different locations for each sample.

[0065] Table 1 Performance test results of Examples 1-11 and Comparative Examples 1-9

[0066] As can be seen from Examples 1 to 3, within the range of carbon black dosage, the room temperature resistivity of each example is at a low level. Among them, the synergistic effect of carbon black and carbon nanotubes is the best when the carbon black dosage is moderate. When the carbon black dosage is low, the elongation at break is higher, which is suitable for application scenarios with high flexibility requirements. When the carbon black dosage is high, the conductivity is still excellent and the gel content remains stable, indicating that the present invention can maintain a good conductive connection structure within a wide range of carbon black filling.

[0067] A comparison of Examples 1 with Examples 4 and 5 shows that when the amount of carboxylated multi-walled carbon nanotubes varies from 1 to 4 parts, the volume resistivity of each example remains at a low level, and the gel content remains above 80%, indicating that the present invention has good tolerance to fluctuations in the amount of carboxylated multi-walled carbon nanotubes. Specifically, the lowest amount of carboxylated multi-walled carbon nanotubes yields higher elongation at break and lower surface roughness; the highest amount results in a decrease in elongation at break and an increase in surface roughness, indicating that the improvement in conductivity from increasing the amount of carboxylated multi-walled carbon nanotubes tends to saturate.

[0068] A comparison of Examples 1 with Examples 6 and 7 shows that when the mass ratio of the total feed amount of 3,4-ethylenedioxythiophene to the total amount of oxidant varies within the range of 0.36 to 0.72, the volume resistivity of each example remains at a low level, while maintaining good conductivity at high temperatures, thus meeting the application requirements for DC cable shielding materials. Increasing the ratio from the lower limit to the middle level significantly improves performance; further increasing it to the upper limit maintains good performance, but the improvement tends to saturate.

[0069] A comparison of Examples 1 with Examples 8 and 9 shows that when the oxidant dosage varies within the range of 6–10 wt% of the total mass of the carbon-based filler, the volume resistivity of each example remains at a low level, while the gel content remains at a high level. This indicates that the present invention can achieve good conductivity and crosslinking effects over a wide range of oxidant dosages. Once the oxidant dosage reaches a certain level, further increasing the dosage has limited effect on improving conductivity, suggesting an optimal dosage range that balances cost and performance.

[0070] A comparison of Example 1 with Examples 10 and 11 shows that, within the spray drying temperature range defined by this invention, shielding materials with good overall performance can be obtained. Spray drying temperature affects the pore volume of porous particles, which in turn affects the loading of the oxidant solution and the polymerization effect of PEDOT, making it a crucial process parameter for controlling the conductive network structure and processing performance.

[0071] The test results of Examples 1-11 and Comparative Examples 1-9 show that, even when PEDOT polymerization is omitted, spray granulation is cancelled, the oxidant is added all at once, carbon nanotubes are not added, unmodified carbon nanotubes are used, no compatibilizer is added, or the amount of 3,4-ethylenedioxythiophene exceeds the limit, the volume resistivity at room temperature and 90°C, as well as the rate of change of resistivity after aging, of each comparative example are higher than those of the embodiments of the present invention. This indicates that the synergistic combination of the above processes and components is beneficial to reducing the volume resistivity of the shielding material and improving the temperature stability and heat aging resistance of its conductive network. Regarding surface roughness, the surface roughness of Comparative Examples 1-7 is higher than that of the embodiments of the present invention, while the surface roughness of Comparative Examples 8 and 9 is closer to that of some embodiments. This indicates that the technical solution of the present invention is generally beneficial to improving the surface quality of the material, but the degree of influence of different technical factors on surface roughness varies. In summary, this invention achieves low volume resistivity, good thermal stability, and good processability in a wide range of formulations through the synergistic effects of porous particle construction, gradient oxidant impregnation, in-situ gas-phase polymerization of 3,4-ethylenedioxythiophene, and interfacial compatibilization.

[0072] like Figure 1 As shown, TEM observations indicate that carbon black particles and carboxylated multi-walled carbon nanotubes form a composite structure within the porous particles. High-magnification TEM and EDS elemental distribution analysis revealed a significant enrichment of sulfur at the interface between the carbon black particles and carbon nanotubes, supporting the presence of abundant PEDOT on the surface and at the interface of the carbon-based filler.

[0073] like Figure 2 As shown, SEM observation results of the conductive masterbatch cross section indicate that the PEDOT bridging carbon-based conductive filler is uniformly dispersed in the ethylene-butyl acrylate copolymer matrix, and there are connection regions between the filler particles, which is beneficial for constructing conductive connection structures.

[0074] like Figure 3 As shown, the volume resistivity of Example 1 increases slowly with increasing temperature, exhibiting good resistivity temperature stability. The volume resistivity of Example 10 is slightly higher than that of Example 1 overall, but the increase with increasing temperature is still relatively small. In contrast, the volume resistivity of Comparative Example 1 is significantly higher than that of Examples 1 and 10 throughout the entire test temperature range, and the increase with increasing temperature is the most significant, exhibiting a significant positive temperature coefficient (PTC) effect. The volume resistivity of Comparative Example 4 is also significantly higher than that of Examples 1 and 10, and its increase with increasing temperature is greater than that of the above examples. The above results indicate that the shielding layer prepared using the PEDOT bridging carbon-based conductive filler of the present invention has good resistivity temperature stability and can effectively suppress the PTC effect.

[0075] The above results demonstrate and describe the basic principles and main features of this application, as well as its advantages.

[0076] Those skilled in the art should understand that this application is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of this application. Various changes and modifications can be made to this application without departing from the spirit and scope thereof, and all such changes and modifications fall within the scope of this application as claimed. The scope of protection of this application is defined by the equivalents of the appended claims.

Claims

1. A method for preparing a cross-linked shielding material for DC cables, characterized in that, Includes the following steps: S1. By weight, 20-35 parts of conductive carbon black and 1-4 parts of carboxylated multi-walled carbon nanotubes are sheared and dispersed in 400-750 parts of an ethanol / water mixed solution. After spray drying, the mixture is lightly rolled and granulated at 2-8 MPa to obtain porous particles. The wettable pore volume per unit mass is determined by mercury intrusion porosimetry. 6-10 wt% of an organic sulfonate iron salt is weighed according to the total mass of the conductive carbon black and carboxylated multi-walled carbon nanotubes. 30%-40% of the total organic sulfonate iron salt is prepared into a 10%-15% organic sulfonate iron salt solution. This solution is sprayed onto the particles at a volume of 20%-30% of the total wettable pore volume of the porous particles, agitated, and then dried under reduced pressure. The remaining 60%-70% of the organic sulfonate iron salt is then taken... Organic sulfonate iron salts were prepared into a 25-35% (w / w) organic sulfonate iron salt solution. This solution was sprayed into the porous particles at a volume of 20-30% of the total wettable pore volume. After agitation and vacuum drying, composite particles were obtained. 3,4-ethylenedioxythiophene vapor was introduced and reacted with the composite particles for 60-180 minutes. The mass ratio of the total 3,4-ethylenedioxythiophene feed to the total amount of organic sulfonate iron salts was (0.36-0.72):

1. After impregnation with an oxidant, 3,4-ethylenedioxythiophene underwent in-situ vapor-phase polymerization on the surface and contact interface of the carbon-based filler, forming a PEDOT bridging layer. After washing and drying, a PEDOT-bridged carbon-based conductive filler was obtained. S2, the total amount of ethylene-butyl acrylate copolymer is 80-90 parts, of which 25-40 parts of ethylene-butyl acrylate copolymer are mixed with the PEDOT bridging carbon conductive filler, and maleic anhydride-grafted ethylene-butyl acrylate copolymer is added as a compatibilizer to prepare conductive masterbatch. The amount of maleic anhydride-grafted ethylene-butyl acrylate copolymer is 5-15% of the total mass of ethylene-butyl acrylate copolymer. S3. The conductive masterbatch is mixed with the remaining ethylene-butyl acrylate copolymer, and antioxidants, lubricants, peroxide crosslinking agents and crosslinking sensitizers are added. After mixing, the mixture is discharged and granulated to obtain crosslinked shielding material.

2. The method for preparing a cross-linked shielding material for DC cables according to claim 1, characterized in that, In S1, the mass ratio of ethanol to water in the ethanol / water mixed solution is (5-9):1; the inlet air temperature of the spray drying is 120-180℃, and the outlet air temperature is 60-90℃; after each spraying, the mixture is turned over for 5-10 minutes and pre-dried under reduced pressure at 40-50℃ for 15-30 minutes.

3. The method for preparing a cross-linked shielding material for DC cables according to claim 1, characterized in that, In S1, the carboxyl content of the carboxylated multi-walled carbon nanotubes is 0.5–5 wt%.

4. The method for preparing a cross-linked shielding material for DC cables according to claim 1, characterized in that, In S1, the organic sulfonate iron salt is p-toluenesulfonate iron; the solvent of the organic sulfonate iron salt solution is n-butanol or a n-butanol / ethanol mixed solvent, wherein the volume ratio of n-butanol to ethanol in the n-butanol / ethanol mixed solvent is (0.8~1.2):

1.

5. The method for preparing a cross-linked shielding material for DC cables according to claim 1, characterized in that, In S1, the 3,4-ethylenedioxythiophene vapor is generated by heating the 3,4-ethylenedioxythiophene monomer to 80-120°C through an independent heating chamber, and an inert gas is introduced as the carrier gas. After the contact is completed, the temperature is raised to 80-100°C at a rate of 1-5°C / min for post-treatment for 10-30min. The pressure under the depressurization condition is 4-20kPa.

6. The method for preparing a cross-linked shielding material for DC cables according to claim 1, characterized in that, In S1, the washing process involves washing with anhydrous ethanol 2 to 4 times and deionized water 3 to 5 times in sequence, until the pH of the final washing solution is 6.5 to 7.

5.

7. The method for preparing a cross-linked shielding material for DC cables according to claim 1, characterized in that, The ethylene-butyl acrylate copolymer contains 15-22 wt% butyl acrylate, and the maleic anhydride-grafted ethylene-butyl acrylate copolymer has a grafting rate of 0.8-1.5%.

8. The method for preparing a cross-linked shielding material for DC cables according to claim 1, characterized in that, The antioxidant is a compound of hindered phenolic antioxidants and phosphite antioxidants; the lubricant is a polyol fatty acid ester; the peroxide crosslinking agent is a dialkyl peroxide; and the crosslinking sensitizer is an allyl compound.

9. A method for preparing a cross-linked shielding material for DC cables according to claim 8, characterized in that, The hindered phenolic antioxidant is antioxidant 1010, the phosphite antioxidant is antioxidant 168, and the mass ratio of the two is (0.8-1.2):1, with a total antioxidant dosage of 0.25-0.45 parts; the polyol fatty acid ester is pentaerythritol stearate, with a dosage of 0.25-0.9 parts; the dialkyl peroxide is 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, with a dosage of 1-2 parts; and the allyl compound is triallyl isocyanurate, with a dosage of 0.3-0.8 parts.

10. A method for preparing a cross-linked shielding material for DC cables according to claim 1, characterized in that, In step S2, after preplasticizing the ethylene-butyl acrylate copolymer and the maleic anhydride-grafted ethylene-butyl acrylate copolymer, the PEDOT bridging carbon-based conductive filler is added, and the mixture is kneaded at a temperature not exceeding 110°C; in step S3, the peroxide crosslinking agent and crosslinking sensitizer are added after the kneading temperature drops below 110°C.